Konstruksi Melalui Identifikasi Perilaku Tidak Aman Berbasis Matriks Risiko - Andi Marwa Muchtar; Achmad Muhyidin Arifa’i (P3M Politeknik Negeri Jember, 2025)
The construction industry remains one of the sectors with the highest occupational accident rates, particularly in large-scale infrastructure projects characterized by complex operations, work at height, heavy equipment utilization, and strict schedule pressures. Unsafe behavior has been widely recognized as a critical contributor to construction accidents; however, quantitative prioritization of such behaviors based on risk levels remains limited. This study aims to identify dominant unsafe behaviors and evaluate their risk levels using a likelihood–severity risk matrix approach within a large-scale construction project. A quantitative cross-sectional survey was conducted involving 96 construction workers. Thirty-eight unsafe behavior indicators were assessed using a five-point Likelihood (L) and Severity (C) scale based on standard risk management principles. Risk levels were calculated using the equation R = L x C, and subsequently classified into low, moderate, high, and extreme categories. The findings indicate that while most unsafe behaviors fall within the moderate risk category, seven indicators were classified as high risk and one indicator reached the extreme risk level. The highest risk was associated with leaving electrical cables exposed or unprotected, followed by fatigue-related behaviors and non-compliance with basic safety procedures such as working without personal protective equipment and inadequate fall protection. These results confirm that unsafe behavior functions as a leading indicator of occupational risk and should be systematically quantified to support priority-based risk control. The study concludes that integrating behavioral risk assessment into risk management frameworks enhances evidence-based decision-making and strengthens safety performance in construction projects.